2012
DOI: 10.4158/ep11371.or
|View full text |Cite
|
Sign up to set email alerts
|

A Retrospective Study Comparing Neutral Protamine Hagedorn Insulin With Glargine As Basal Therapy In Prednisone-Associated Diabetes Mellitus In Hospitalized Patients

Abstract: Objective To compare glycemic outcomes in hospitalized patients with or without type 2 diabetes mellitus receiving neutral protamine Hagedorn insulin (NPH) vs glargine as basal insulin for management of glucocorticoid-associated hyperglycemia. Methods We conducted a retrospective review of electronic medical records in prednisone-treated adult patients with hyperglycemia in a university hospital. Consecutive patients were selected in both the NPH and glargine cohorts using inclusion and exclusion criteria. B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
44
1
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(49 citation statements)
references
References 23 publications
1
44
1
3
Order By: Relevance
“…A recent study reported that hospitalised patients on prednisone administered insulin glargine and insulin isophane had similar fasting and mean daily glucose concentrations . However, patients in that study receiving insulin glargine were prescribed a higher daily insulin dose than those prescribed insulin isophane .…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…A recent study reported that hospitalised patients on prednisone administered insulin glargine and insulin isophane had similar fasting and mean daily glucose concentrations . However, patients in that study receiving insulin glargine were prescribed a higher daily insulin dose than those prescribed insulin isophane .…”
Section: Discussionmentioning
confidence: 96%
“…20 However, patients in that study receiving insulin glargine were prescribed a higher daily insulin dose than those prescribed insulin isophane. 20 Furthermore, the effect of the two insulin regimens at different time points was not dissected. 20 Our results suggest that further research is needed to define the most effective insulin regimen to treat prednisolone-induced hyperglycaemia, as highlighted in a recent call to action to improve management of inpatient hyperglycaemia.…”
Section: Figurementioning
confidence: 95%
See 1 more Smart Citation
“…9 A recent study showed that administration of NPH and glargine as basal insulin were equally effective in treating patients with prednisone-induce hyperglycemia. 16 Seggelke et al performed a small study in patients with cystic fibrosis receiving methylprednisolone, assessing glucose outcomes in patients treated with glargine and lispro compared with glargine, lispro, and NPH. 17 Results showed that both treatment groups had similar (normoglycemic) fasting blood glucose levels; however, the group that received NPH in addition to the basal-bolus regimen had better pre-lunch and pre-dinner glucose levels.…”
Section: Discussionmentioning
confidence: 99%
“…Although without statistically significat difference, in both articles was found more rate of hypoglycemia in NPH group. [46,47] Surgery Hyperglycemia is associated with increased risk for adverse outcomes in patients undergoing surgery: more length of stay, postoperative complications, infections, and more mortality. [48,49] The recommendations and the treatment depend on the type of diabetes, surgical procedure, when patient is going to resume feeding, previous diabetic treatment, glucose control, and metabolic state of patients.…”
Section: Journal Of Translational Internal Medicine / Oct-dec 2016 / mentioning
confidence: 99%